Analisis Kelayakan Finansial Usaha Ternak Ayam Joper Di Kabupaten Karanganyar - Imani, Cahya Sekar; Erlyna Wida Riptanti; Rhina Uchyani Fajarningsih (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
The Joper chicken in Karanganyar Regency, Central Java, becomes an alternative to replace ordinary village chickens because it has the same quality but a shorter harvesting period, but it Â has uncertain fluctuations every year. This Fact is interesting to find out the feasibility of Joper chickens. We aims to analyse the feasibility of joper chicken and to identify the Break Even Point (BEP) of Joper chicken in Karanganyar Regency. We uses snowball sampling technique with a total of 60 farmers in four districts, including Jumantono, Karangpandan, Ngargoyoso, and Mojogedang. We uses primary and secondary data. A feasibility analysis was carried out namely NPV, IRR, Net B/C Ratio, Payback Period, and BEP. The results show that at an interest rate of 6% and an economic life of 10 years, Joper chicken farming in Karanganyar Regency is feasible to be cultivated because the NPV is Rp 67,418,062, the IRR is 13% > discount rate 6%, the Net B/C Ratio is 1.49 with criteria > 1 then it feasible to run, the Payback Period is 3 years which is smaller then the project age of 10 years and the BEP is 747 Kg/Year and Rp 26,821,397 per year.